Working Together in Vanuatu Research Histories, Collaborations, Projects and Reflections - Taylor, J. (ANU Press, 2011)
This collection is derived from a conference held at the Vanuatu National Museum and Cultural Centre (VCC) that brought together a large gathering of foreign and indigenous researchers to discuss diverse perspectives relating to the unique program of social, political and historical research and management that has been fostered in that island nation. While not diminishing the importance of individual or sole-authored methodologies, project-centered collaborative approaches have today become a defining characteristic of Vanuatu's unique research environment. As this volume attests, this environment has included a dynamically wide range of both ni-Vanuatu and foreign researchers and related research perspectives, most centrally including archaeologists and anthropologists, linguists, historians, legal studies scholars and development practitioners. This emphasis on collaboration has emerged from an ongoing awareness across Vanuatu's research community of the need for trained researchers to engage directly with pressing social and ethical concerns, and out of the proven fact that it is not just from the outcomes of research that communities or individuals may be empowered, but also through their modes and processes of implementation, as through the ongoing strength and value of the relationships they produce. With this in mind, the papers presented here go beyond the mere celebration of collaboration by demonstrating Vanuatu's specific environment of cross-cultural research as a diffuse set of historically emergent methodological approaches, and by showing how these work in actual practice.